Six ways to get a grip on your first health education leadership role - Stasiuk, Samantha; Scott, Ian (Canadian Medical Education Journal, 2021)
Entering into health education leadership with clear intentions can help guide a new career. While being asked, or simply considering, an educational leadership position, is exciting, it is important to consider your motivation for this position, how this position will mesh with your life and what you want to achieve in this position. In addition, it is important to look to mentors for advice and consider other avenues of professional development. Our six tips provide insight into the consideration, negotiation and selection of a health education leadership career that can yield numerous rewards both personally and professionally.